Severe T-System Remodeling in Pediatric Viral Myocarditis - Fiegle, Dominik J.; Schöber, Martin; Dittrich, Sven; Cesnjevar, Robert; Klingel, Karin; Volk, Tilmann; Alkassar, Muhannad; Seidel, Thomas (Frontiers in Cardiovascular Medicine, 2021)
Chronic heart failure (HF) in adults causes remodeling of the cardiomyocyte transverse tubular system (t-system), which contributes to disease progression by impairing excitation-contraction (EC) coupling. However, it is unknown if t-system remodeling occurs in pediatric heart failure. This study investigated the t-system in pediatric viral myocarditis. The t-system and integrity of EC coupling junctions (co-localization of L-type Ca2+ channels with ryanodine receptors and junctophilin-2) were analyzed by 3D confocal microscopy in left-ventricular (LV) samples from 5 children with myocarditis (age 14±3 months), undergoing ventricular assist device (VAD) implantation, and 5 children with atrioventricular septum defect (AVSD, age 17±3 months), undergoing corrective surgery. LV ejection fraction (EF) was 58.4±2.3% in AVSD and 12.2±2.4% in acute myocarditis. Cardiomyocytes from myocarditis samples showed increased t-tubule distance (1.27±0.05µm, n=34 cells) and dilation of t-tubules (volume-length ratio: 0.64±0.02µm2) when compared with AVSD (0.90±0.02µm, p<0.001; 0.52±0.02µm2, n=61, p<0.01). Intriguingly, 4 out of 5 myocarditis samples exhibited sheet-like t-tubules (t-sheets), a characteristic feature of adult chronic heart failure. The fraction of extracellular matrix was slightly higher in myocarditis (26.6±1.4%) than in AVSD samples (24.4±0.8%, p<0.05). In one case of myocarditis, a second biopsy was taken and analyzed at VAD explantation after extensive cardiac recovery (EF from 7% to 56%) and clinical remission. When compared with pre-VAD, t-tubule distance and density were unchanged, as well as volume-length ratio (0.67±0.04µm2 vs 0.72±0.05µm2, p=0.5), reflecting extant t-sheets. However, junctophilin-2 cluster density was considerably higher (0.12±0.02µm-3 vs 0.05±0.01µm-3, n=9/10, p<0.001), approaching values of AVSD (0.13±0.05µm-3, n=56), and the measure of intact EC coupling junctions showed a distinct increase (20.2±5.0% vs 6.8±2.2%, p<0.001). Severe t-system loss and remodeling to t-sheets can occur in acute HF in young children, resembling the structural changes of chronically failing adult hearts. T-system remodeling might contribute to cardiac dysfunction in viral myocarditis. Although t-system recovery remains elusive, recovery of EC coupling junctions may be possible and deserves further investigation.